Clustering techniques for web mining - Sanusi, Emil. (2010)
The project mainly focuses on the design and implementation of two newly proposed data clustering algorithms, namely Active Fuzzy Constrained Clustering (AFCC) and Semi-Supervised Heuristic Fuzzy Co-clustering with the Ruspini’s condition (SS-HFCR), for semi-supervised data analysis.